Inovasi Teknologi Wearable Gaming dalam PkM KKN: Upaya Peningkatan Kualitas Pembelajaran di Sekolah Dasar - Rihatno, Taufik; Nuraini, Sri; Wahyudiana, Endang; Akbar, Zidane; Al Furqon, Rozaqi; Asy-Syamiil, Grandy Jiddan; Nugraha, Daffa Setyo; Bowoleksono, Tegar; Dewiyani, Leola; Marini, Arita (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2025)
The strategic need to implement a teacher empowerment program at SDN Tanah Tinggi 05 Pagi through the utilization of Wearable Gaming Technology as an innovative approach to enhance students’ learning interest is driven by the demand for a more interactive, contextual, and technology-integrated learning process. This technology offers opportunities for teachers to create more engaging, immersive, and enjoyable learning experiences, thereby encouraging active student participation in classroom activities. Moreover, the appropriate implementation of wearable gaming supports the development of critical thinking, communication, collaboration, and creativity—key 21st-century skills. This initiative aims to improve teachers' digital literacy and professional capacity in designing and integrating technology effectively into the learning process. Through a Community Service (PkM) program integrated with the Student Community Service Program (KKN), the initiative has shown positive outcomes, including enhanced teacher understanding of wearable technology and the ability to design gamified learning strategies that are interactive, collaborative, and capable of boosting student motivation and conceptual understanding. This competency enhancement is expected to transform teachers into innovative, responsive, and adaptive learning facilitators in line with the rapid technological advancements in education.